2020
DOI: 10.3390/s20020391
|View full text |Cite
|
Sign up to set email alerts
|

Multi-GPU, Multi-Node Algorithms for Acceleration of Image Reconstruction in 3D Electrical Capacitance Tomography in Heterogeneous Distributed System

Abstract: Electrical capacitance tomography (ECT) is one of non-invasive visualization techniques which can be used for industrial process monitoring. However, acquiring images trough 3D ECT often requires performing time consuming complex computations on large size matrices. Therefore, a new parallel approach for 3D ECT image reconstruction is proposed, which is based on application of multi-GPU, multi-node algorithms in heterogeneous distributed system. This solution allows to speed up the required data processing. Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…While experimental techniques can precisely measure the actual system performance, this way may have strong pertinence and is lack of generality. Moreover, our system model mainly discusses the problem of cross-server task offloading and forwarding, which does not consider how to dispense one computational task to different edge servers in MEC, especially in heterogeneous distributed system [32].…”
Section: Discussionmentioning
confidence: 99%
“…While experimental techniques can precisely measure the actual system performance, this way may have strong pertinence and is lack of generality. Moreover, our system model mainly discusses the problem of cross-server task offloading and forwarding, which does not consider how to dispense one computational task to different edge servers in MEC, especially in heterogeneous distributed system [32].…”
Section: Discussionmentioning
confidence: 99%
“…The ERT machines for 3D data acquisition are regularly tested for speed and accuracy [ 65 ]. High-speed ERT and ECT systems using parallel computing on multi-GPU in a heterogeneous system [ 66 ], FPGA electronics [ 13 , 67 ], with parallel and multiplanar ERT systems [ 68 ], and rapid estimation algorithms using artificial neural networks [ 69 ] have been designed to evaluate various process tomographic parameters.…”
Section: Ert Imagingmentioning
confidence: 99%
“…The standard methods that use the finite element method (FEM) can calculate the electric field at each element (for instance, with triangle shape) of the FEM mesh. Banasiak et al [ 24 , 25 ] showed that the sensitivity matrix can also be calculated at nodes. It helps to reduce the number of values consequently in the sensitivity matrix and can decrease the under-determination degree of an inverse problem.…”
Section: Image Reconstructionmentioning
confidence: 99%